Hubungan Beban Kerja Fisik dan Beban Kerja Mental terhadap Kelelahan Kerja pada Pekerja Las PT PAL Indonesia - Sahilah Amrina Rosadah; Denny Ardyanto; Ayik Mirayanti Mandagi; Bian Shabri Putri Irwanto (INSOLOGI: Jurnal Sains dan Teknologi, 2024)
Work fatigue in the shipping industry needs attention. Based on 2018 ILO data, it is stated that more than 2 million workers in the world die every year due to fatigue caused by work-related diseases or work accidents. Fatigue can be caused by an imbalance in workload. The workload, both physical and mental, must be in accordance with the worker's abilities. Physical load is dominated by physical activity work while mental load is dominated by mental activity or thinking. The aim of this research is to analyze the strong relationship between mental workload and physical workload on work fatigue. The research method includes descriptive research with an observational research design and a cross-sectional approach on welding 1 and welding 2 workers in the commercial division of PT PAL Indonesia. The strength of the relationship between the dependent variable and the independent variable is seen based on the results of the correlation coefficient (r) in the Spearman test. The results of the research show that there is a very strong relationship between mental workload and work fatigue of 0.811 (very strong) between physical workload and work fatigue of 0.847 (very strong). The strong relationship between physical workload and work fatigue is greater than the strong relationship between mental workload and work fatigue.